RESEARCH ON THE RELATIONSHIP BETWEEN FINANCIAL TRANSPARENCY AND ACCOUNTABILITY BASED ON STUDENT PERCEPTIONS IN E-GOVERNMENT IMPLEMENTATION: A STUDY IN BANDUNG CITY, INDONESIA - Dini Arwaty; Dini Verdania Latif (Jurnal Ekonomi, 2023)
The application of digital technology has been carried out since the 1990s, known as e-government. E-government is expected to provide easy access to information for the public, especially in the financial sector, so that an accountable government can be created. This study aims to examine the relationship between transparency and financial accountability in the implementation of e-government. This research is correlational research. This research was conducted on the implementation of e-government in the city of Bandung. The sample was Bandung University students who have knowledge about e-government and have used it. The results showed that there is a relationship between financial transparency and accountability in e-government implementation. The existence of financial transparency creates the perception of citizens that the government is responsible in carrying out its functions. In addition, it educates citizens about the use and benefits of e-government for them.